Recurrence of nephrolithiasis: incidence and risk factors in Egyptian patients - Mostafa M Ebraheem; Alsayed S Abdelaziz; Ayman M Ghoneem; Esam A Elnady (Wolters Kluwer Medknow Publications, 2020)
Introduction Recurrence of nephrolithiasis is common. The knowledge of its incidence and risk factors is the base for proper prophylaxis and preservation of renal function. Objective The aim was To study the recurrence rate and risk factors of nephrolithiasis in Egyptian patients. Patients and methods Files of 974 patients with nephrolithiasis (634 males and 340 females, aged 7-70 years) were reviewed. They were managed between 2008 and 2009, with a 10-year follow-up period since the first stone episode for recurrence. Stone characteristics (sizes, sites, and multiplicity), treatment type, post-treatment residual stones, family history, BMI, and recurrence rate were included. Results Of the 974 patients, stone recurrence rate was 44.45% within 10 years of follow-up. Recurrence was significantly higher in young age group of less than 20 years, male sex, average BMI, and positive family history (61.14, 52.99, 50.99, and 55.82%, respectively) within 10 years. Recurrence was significantly higher with stone size greater than 2 cm (24.20%) at the second 5-year follow-up. Recurrence was significantly higher with multiple (56.59%), pelvicalyceal (59.83%), and bilateral (66.95%) renal stones within 10 years. It was significantly higher with shock wave lithotripsy (20.89%) within the second 5-year follow-up, and with presence of residual stones (32.66%) within the first 5-year follow-up. Conclusion Stone recurrence rate increases with increase in observation time. Risk factors for recurrence are young age of onset; male sex; normal BMI; positive family history; large size, multiple, bilateral, and pelvicalyceal stone; shock wave lithotripsy treatment; and presence of residual stones.